PEMERINTAHAN ABU BAKAR : TINJAUAN SEJARAH TERHADAP SISTEM DAN DINAMIKA PEMERINTAHAN - Maruli Tumangger (TAQNIN: Jurnal Syariah dan Hukum, 2021)
Abu Bakr was a prominent companion of the Messenger of Allah, and one of those guaranteed to enter Paradise. His defense of Islam, especially to the Prophet Muhammad, was so great that he was known by his title ash-Siddiq which means always justifying, because he always confirmed the prophetic messages of the Prophet Muhammad. He was also the first caliph in the history of Islamic rule. The existence of the Abu Bakr government is very important because after the death of the Prophet Muhammad, there were various debates on who was worthy and worthy to occupy the position as leader of the Muslims. This paper seeks to reveal various aspects and dynamics that occurred in the government of Abu Bakr and the system of government that he runs. The discussion of this paper will begin by explaining Abu Bakr's brief biography, the process of being appointed as the first caliph and ending with explaining the dynamics and system of his government.